Wpływ rehabilitacji neurologicznej na funkcjonowanie pacjentów po przebytym udarze niedokrwiennym mózgu – analiza retrospektywna = The influence of neurological rehabilitation on the functioning of patients after ischemic stroke – a retrospective analysis - Kałużny, Krystian; Kałużna, Anna; Kochański, Bartosz; Cichosz, Michał; Płoszaj, Ola; Pawiłan, Michalina; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2016)
Kałużny Krystian, Kałużna Anna, Kochański Bartosz, Cichosz Michał, Płoszaj Ola, Pawiłan Michalina, Zukow Walery, Hagner Wojciech. Wpływ rehabilitacji neurologicznej na funkcjonowanie pacjentów po przebytym udarze niedokrwiennym mózgu – analiza retrospektywna = The influence of neurological rehabilitation on the functioning of patients after ischemic stroke – a retrospective analysis. Journal of Education, Health and Sport. 2016;6(12):38-52. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192164 http://ojs.ukw.edu.pl/index.php/johs/article/view/4031 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 01.12.2016. Wpływ rehabilitacji neurologicznej na funkcjonowanie pacjentów po przebytym udarze niedokrwiennym mózgu – analiza retrospektywna The influence of neurological rehabilitation on the functioning of patients after ischemic stroke – a retrospective analysis Krystian Kałużny1, Anna Kałużna1,2, Bartosz Kochański1, Michał Cichosz3,4, Ola Płoszaj5, Michalina Pawiłan1, Walery Zukow6, Wojciech Hagner1 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy 2 Katedra Chorób Naczyń i Chorób Wewnętrznych, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy 3 Oddział Rehabilitacji Neurologicznej, Jolly Med, Popielówek 4 Fundacja Wsparcie, Kowary 5 Bydgoska Szkoła Wyższa 6 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: udar mózgu, rehabilitacja, PNF, skala Barthel Key words: stroke, rehabilitation, PNF, the scale of Barthel Streszczenie Wstęp: Funkcjonowanie pacjentów po udarze niedokrwiennym mózgu jest źródłem zainteresowania dla wielu badaczy oraz ogromnym wyzwaniem dla współczesnej medycyny. Według danych Światowej Organizacji Zdrowia (WHO) udar mózgu jest trzecią co do częstości przyczyną zgonu (po chorobach serca i nowotworach) oraz najczęstszą przyczyną ciężkiego inwalidztwa w populacji osób powyżej 45 roku życia, co niesie za sobą istotne następstwa kliniczne, socjalne i ekonomiczne. Cel pracy: Celem pracy była ocena skuteczności zastosowanej rehabilitacji neurologicznej u pacjentów po udarze niedokrwiennym mózgu, ocena funkcjonowania pacjentów po udarze niedokrwiennym mózgu poddanych rehabilitacji neurologicznej oraz ocena wpływu czynników dodatkowych na skuteczność rehabilitacji neurologicznej. Materiał i metody: Badaną grupę stanowiło 30 osób obu płci (15 kobiet i 15 mężczyzn) w wieku 47-78 lat po przebytym udarze niedokrwiennym mózgu, których poprawę funkcjonowania w wyniku procesu rehabilitacji oceniano wybranymi elementami skali Barthel. Badania przeprowadzone zostały na podstawie analizy historii chorób pacjentów hospitalizowanych w Klinice Rehabilitacji Szpitala Uniwersyteckiego nr 1 w Bydgoszczy w latach 2015-2016. Wykorzystano autorski kwestionariusz ankiety sondażowej zawierającym wybrane elementy skali Barthel. Wyniki: W badanej grupie statystycznie istotnie częściej występowały osoby ze środowiska wiejskiego, u których stwierdzono współistniejące choroby tj. nadciśnienie tętnicze, migotanie przedsionków, cukrzyca, choroba niedokrwienna serca i inne. Wśród pacjentów przekazanych bezpośrednio z Centrum Leczenia Udarów Mózgu do Kliniki Rehabilitacji u ponad połowy pacjentów zaobserwowano poprawę funkcjonowania w przeciągu 1 miesiąca pobytu, natomiast z pacjentów korzystających z rehabilitacji wtórnej poprawę funkcjonalną zaobserwowano tylko u co czwartego pacjenta. Wnioski: 1) Rehabilitacja neurologiczna istotnie wpływa na funkcjonowanie pacjentów po udarze niedokrwiennym mózgu. 2) Rehabilitacja wdrożona we wczesnym okresie po udarze niedokrwiennym mózgu ma znamiennie wyższą efektywność co przekłada się na większą poprawę stanu funkcjonalnego pacjentów po udarze niedokrwiennym mózgu. 3) Zastosowanie metody PNF i NDT-Bobath istotnie wpływa na poprawę stanu funkcjonalnego pacjentów po udarze niedokrwiennym mózgu. Abstract Introduction: The functioning of patients after ischemic stroke is a source of interest to many researchers and a huge challenge for modern medicine. According to the World Health Organization (WHO), stroke is the third leading cause of death (after heart disease and cancer) and the leading cause of severe disability in the population of people over the age of 45, which would have important clinical consequences, social and economic. Aim: The aim of this study was to assess the effectiveness of the applied neurological rehabilitation of patients after ischemic stroke, the assessment of the functioning of patients after ischemic stroke underwent neurological rehabilitation and assessment of the impact of additional factors on the effectiveness of neurological rehabilitation. Material and methods: The study group consisted of 30 people of both sexes (15 females and 15 males) aged 47-78 years after ischemic stroke, which improve the operation as a result of the rehabilitation process was assessed as certain aspects Barthel. The study were conducted on the basis of the analysis of medical history of patients hospitalized in the Clinic of Rehabilitation, University Hospital No. 1 in Bydgoszcz in the years 2015-2016. Used our own questionnaire sounding containing selected elements Barthel. Results: In the study group was statistically significantly more frequent in people from the rural diagnosed with comorbid disease, ie. hypertension, atrial fibrillation, diabetes, coronary heart disease, and others. Among patients transferred directly from the Center for Stroke Treatment to the Clinic of Rehabilitation in more than half of the patients experienced an improvement in functioning within 1 month stay, while the rehabilitation of patients with secondary functional improvement was observed only in every fourth patient. Conclusions: 1) Rehabilitation of neurological significantly affects the functioning of patients after ischemic stroke. 2) Rehabilitation implemented early after ischemic stroke is significantly higher efficiency which translates into a greater improvement in the functional status of patients after ischemic stroke. 3) Application of PNF and NDT-Bobath method significantly improves the functional status of patients after ischemic stroke.